Memorialization Practices Are Changing: An Industry Perspective on Improving Service Outcomes for the Bereaved. (November 2021) - Lowe, Jennifer; Rumbold, Bruce; Aoun, Samar M.
Although considerable research efforts have focused on bereavement outcomes following loss, there are few studies which address the role of memorialization, particularly as it relates to formal service provision. Currently the funeral, cemetery, and crematorium industries are observing a steady decline in traditional and formal memorialization practices. This study aims to identify current memorialization practices and emerging trends, highlight key priorities for improving service outcomes for the bereaved, and understand the implications of changing consumer preferences for service provision. The study's qualitative research design incorporates two phases, a scoping literature review followed by in-depth interviews with eight service providers from the funeral, cemetery, and crematorium industries. A key finding is that the trend toward contemporary and informal memorialization practices blurs the lines between the role of consumers and service providers. There is a clear opportunity for service providers to engage in community education as a means of building supportive relationships with and improving service outcomes for the bereaved.